Development of unmanned aerial vehicles maintenance strategy under an asset management framework - Gonçalves, P. (2018)
Many organizations in a large number of countries all around the world are now awaking for a new reality concerning potential applications for the usage of unmanned aerial vehicles (UAV) or unmanned aerial systems (UAS). What was initially strictly applied for military purposes or pure private entertainment has now widespread for other purposes as for example for book or pizza delivery to customers. In manned commercial and military aircraft the MSG (Maintenance Steering Group) philosophy is usually followed and is the root of all inspection schedules in a process starting before an aircraft enters service. However, for the UAV (or UAS), as a system, there are not yet such procedures and each operator establishes the needed requirements on the development stage. The question is how to integrate this type of equipment in an asset management framework as presented in the PAS 55 or the recent ISO 55000. The objective of this paper is to show an exemple of the development of a UAV where these issues are discussed and some proposals to integrate them on an asset management framework regarding the design for effectiveness and design for safety are made on an early stage of an asset engineering process.